ANALISIS KANDUNGAN LOGAM TIMBAL PADA SAYUR KANGKUNG DAN BAYAM DI JALAN KARTAMA PEKANBARU SECARA SPEKTROFOTOMETERI SERAPAN ATOM - Pinta Erdayanti; Tengku Abu Hanifah; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Vegetable has a lot of vitamins and minerals that useful for people. Therefore, hygiene and safety of vegetables consumed are important for healthiness. Many types of vegetables that circulated in the community were unsafe because allegedly contaminated with heavy metals such as lead, especially the vegetables planted in the roadside. The aims of this study is to determine the metal content of Pb in vegetable water spinach, spinach and soil sample which planted in Kartama street Pekanbaru. Lead content was determined using an atomic absorption spectrophotometer at the wavelength of 283.3 nm. The results showed that the highest of Pb was found in spinach (0.4234 mg/Kg) and soil sample that the spinach planted (1.6418 mg/Kg) was taken from ST1. The result of this study indicates that the sample spinach contains Pb that did not exceed the maximum limit of standar nasional (SNI 01-7387-2009) that is 5 mg/Kg and soil sample is 10 mg/Kg.